Visual and label-free ASFV and PCV2 detection by CRISPR-Cas12a combined with G-quadruplex - Wang, Ying; Li, Rong; Zhang, Yang; Zhang, Weida; Hu, Sishun; Li, Zili (Frontiers in Veterinary Science, 2022)
African Swine Fever (ASF) and Postweaning Multisystemic Wasting Syndrome (PMWS) are acute infectious diseases caused by African swine fever virus and Porcine Circovirus type 2 (PCV2). At present, there is no effective vaccines for the prevention of ASFV. PMWS, which is harmful to the domestic and even the world pig industry, is difficult to cure and has a high mortality. So, developing simple, inexpensive, and accurate analytical method to detect and effectively diagnose ASFV and PCV2 can be conducive to avoid ASFV and PCV2 infection. CRISPR has become a potentially rapid diagnostic tool due to recent discoveries of the trans cleavage properties of CRISPR type V effectors. Herein, we report the visual detection based on CRISPR-Cas12a (cpf1) which is more convenient than fluorescence detection. Through in vitro cleavage target DNA activation, Cas12a can trans-cleavage ssDNA G-quadruplex. TMB/H2O2 and Hemin can't be catalysed by cleavaged G-DNA to produce green color products. This protocol is useful for the detection of ASFV and PCV2 with high sensitivity. This method can enable the development of visual, label-free ASFV and PCV2 detection and can be carried out in the field without relying on instruments or power. This method can complete nucleic acid detection at 37 ℃ without using other instruments or energy. Our research has expanded the application of Cas12a and laid the foundation for the field rapid detection of viral nucleic acid in the future.